CEO inside debt and the value of excess cash. Issue 2 (14th May 2018) - Belkhir, Mohamed; Boubaker, Sabri; Chebbi, Kaouther
Abstract : Purpose: The purpose of this paper is to investigate the relationship between corporate debt-like compensation and the value of excess cash holdings. Design/methodology/approach: The sample comprises 876 US firms covered by ExecuComp over the period 2006-2013. The authors apply the valuation regression of Fama and French (1998) to examine the marginal value of excess cash as a function of CEO inside debt holdings. Findings: This paper proposes one hypothesis. The results constitute evidence that the value of excess cash to shareholders declines as CEO inside debt increases. More interestingly, excess cash holdings contribute less to firm value when shareholders expect their value to be destroyed due to managers' conservative behavior. Research limitations/implications: The sample comprises only US firms, owing to a lack of firms data from other countries. It would be interesting to conduct future research on an international sample. Practical implications: This paper contributes to a deeper understanding of investor valuation of excess cash in the presence of CEO inside debt. The findings complement previous studies on US firms by confirming the existence of a relationship between the agency costs of debt and firm policy decisions. Originality/value: This work is, to the best of the authors' knowledge, the first to examine the relationship between debt-like compensation and excess cash valuation, and it supports the view that the conflict between shareholders and debtholders largely affects firm cash policy, and hence, cash valuation.